Retrospective economic analysis of the transfer of services from hospitals to the community: an application to an enhanced eye care service. Issue 7 (10th July 2017) - Mason, Thomas; Jones, Cheryl; Sutton, Matt; Konstantakopoulou, Evgenia; Edgar, David F; Harper, Robert A; Birch, Stephen; Lawrenson, John G
Abstract : Objective: This research aims to evaluate the wider health system effects of the introduction of an intermediate-tier service for eye care. Setting: This research employs the Minor Eye Conditions Scheme (MECS), an intermediate-tier eye care service introduced in two London boroughs, Lewisham and Lambeth, in April 2013. Design: Retrospective difference-in-differences analysis comparing changes over time in service use and costs between April 2011 and October 2014 in two commissioning areas that introduced an intermediate-tier service programme with changes in a neighbouring area that did not introduce the programme. Data sources: MECS audit data; unit costs for MECS visits; volumes of first and follow-up outpatient attendances to hospital ophthalmology; the national schedule of reference costs. Main outcome measures: Volumes and costs of patients treated. Results: In one intervention area (Lewisham), general practitioner (GP) referrals to hospital ophthalmology decreased differentially by 75.2% (95% CI −0.918% to −0.587%) for first attendances, and by 40.3% for follow-ups (95% CI −0.489% to −0.316%). GP referrals to hospital ophthalmology decreased differentially by 30.2% (95% CI −0.468% to −0.137%) for first attendances in the other intervention area (Lambeth). Costs increased by 3.1% in the comparison area between 2011/2012 and 2013/2014. Over the same period, costs increased by less (2.5%) in one intervention area and fell by 13.8% in the other intervention area. Conclusions: Intermediate-tier services based in the community could potentially reduce volumes of patients referred to hospitals by GPs and provide replacement services at lower unit costs.